AB1175 BIOLOGICAL THERAPY DOSE OPTIMIZATION AND COST MINIMIZATION STUDY IN SPONDYLOARTHRITIS: UTILITY OF REDOSER TOOL. (2nd June 2020) - Godoy-Navarrete, F.; Manrique Arija, S.; Osorio, F.; Cabezas-Lucena, A. M.; Morales-Águila, M.; Jiménez-Núñez, F. G.
Abstract : Background: Objectives: . To describe the percentage of spondyloarthritis patients on biological therapy (BT) optimization in clinical practice whowould maintain remission or low disease activity (LDA) after 2 years of follow-up and to identify possible factors associated with relapse. To estimate the cost reduction between 2009-19 Methods: Design: A retrospective, observational longitudinal study under conditions of clinical practice. Patients: Spondyloarthritis in BT dose reduction. Inclusion criteria: Psoriatic arthritis (CASPAR criteria), and Axial Spondyloarthritis (ASAS criteria) which have been iniciated BT dose reduction between 2009-2019. Patients with BT are followed prospectively by two rheumatologists in a monographic clinic of subcutaneous biological therapy every 6 months, and with their usual rheumatologist every 6 months, as well. In such, the patients are controlled and attended in clinics with a pre-established questionnaire every 3 months. Variables: Maintained Reduction: patients who maintained BT dose reduction since de beginning of the optimization until the index date(data collection). Relapse at 3, 6, 12, 24 months : patient who had to returnt to usual BT dose. Other variables: demographic, time to diagnosis and evolution disease, clinical-analytical: Tender Joint Count(TJC), Swollen Joint Count (SJC), C-reactive Protein (CRP), Erythrocyte Sedimentation Rate (ESR), activity index: DAPSA; BASDAI, ASDAS and physical function: HAQ and BASFI. Previous treatment with bDMARD. Dose reduction adjustment according to REDOSER. Cost reduction in euros (absolute and per patient-year) of BT in patients who are in dose reduction compared to the standard care. Analysis: Descriptive, Bivariate analysis, Multivariate logistic regression (DV:relapse). The absolute cost reduction and per patient-year was calculated. Results: 65 patients with spondyloarthritis in dose reduction were included. Table 1 main characteristics in study population. The average time since the beginning of the BT was 47.61 months (±37.06). After 24 months of follow-up, 73.8% of patients (48) achieved a sustained reduction. All these patients accomplish remission or low disease according to differente index activities [DAPSA and BASDAI median(p25-p75)= 2.3 (2.1- 2.9) and 1.5 (0.7- 2.6), respectively and ASDAS mean (SD) =1.4 (0.54)] and a shorter time of disease evolution. The dose reduction of BT carried out from 2009 to 2019 meant a total cost savings of 584080.37€, with a patient/year cost savings of 6192.28€. We evaluated the optimization according to REDOSER and it was observed that in 53 patients (81.5%) the reduction would have been adequate and the rest was doubtful. In bivariant analysis between patients who had relapsed and those who had not, only differences were observed in the BT line used [2nd line:(5(29.4%) Vs 2(4.2%), (p=0.025)] and and a higher percentage of patients with a doubt result of REDOSER [9(52.9%)Vs 3(6.3%), p<0.001)] respectively. In multivariant analysis the only independent variable associated with relapse was a doutbful result of REDOSER[OR(IC95%), 3.46(1.18-10.17); p=0.024], R2= 40.2% Figure 1: Conclusion: Biological therapy dose reduction in spondyloarthritis is possible in the majority of patients, maintaining remission/LDA at 24 months. This leads to a greater cost reduction and efficiency. The relapse was associated with a doubtful result in REDOSER before optimization and this tool can be very useful in the assessment of BT reduction. Disclosure of Interests: None declared